CHOICE OF ORGANIZATIONAL FORMS FOR CONSTRUCTION OF RESIDENTIAL OBJECTS TAKING INTO ACCOUNT INTERESTS AND ABILITIES OF DIFFERENT PARTICIPANTS - Tytok Victoriya Viktorovna (European Scientific Journal, ESJ, 2015)
The great value has the choice of organizational forms for construction management at organization of construction production. Choice of any organizational form to perform particular project depends on number of factors: customer`s and investor`s wishes, contractor`s abilities, specific character of construction object.